Profiling of clinical characteristics of stroke in young - ISH experience - Premalatha BS; Swetha G; Sujatha S; Deepthi Dechamma; Namratha R; Ruby Sunny (Journal of All India Institute of Speech and Hearing, 1970)
The impact of stroke on the individual's family and society is strongest when it aects a young individual. The study pro les the characteristics of stroke in young individuals, onset of stroke, age, gender, education, occupation, family history of stroke/other disability, aetiology, radiological ndings, assessment by SLP for language intervention, therapy sessionsand prognosis of 52 individuals with adult neurogenic speech and language disorders in the age range of 15-49 years . More men suer (30%) with stroke than women,46(88%) had sudden onset of stroke whereas 6 (12%) reported of gradual onset, 5 had a positive family history of stroke and 7 reported of other illness. Majorities had completed graduation andwere skilled. As observed in the study, occurrence of stroke related to a single cause was found to be the most common among young individuals.